Offshore multi-purpose platforms for a Blue Growth: a technological, environmental and socio-economic review - Abhinav, K. A.; Collu, Maurizio; Benjamins, Steven; Cai, Huiwen; Hughes, Adam; Jiang, Bo; Jude, Simon; Leithead, William; Lin, Cui; Liu, Hongda; Recalde-Camacho, Luis; Serpetti, Natalia; et al. (Elsevier, 2020)
“Blue Growth” and “Blue Economy” is defined by the World Bank as: “the sustainable use of ocean resources for economic growth, improved livelihoods and jobs, while preserving the health of ocean ecosystem”. Multi-purpose platforms (MPPs) can be defined as offshore platforms serving the needs of multiple offshore industries (energy and aquaculture), aim at exploiting the synergies and managing the tensions arising when closely co-locating systems from these industries. Despite a number of previous projects aimed at assessing, from a multidisciplinary point of view, the feasibility of multipurpose platforms, it is here shown that the state-of-the-art has focused mainly on single-purpose devices, and adopting a single discipline (either economic, or social, or technological, or environmental) approach. Therefore, the aim of the present study is to provide a multidisciplinary state of the art review on, whenever possible, multi-purpose platforms, complementing it with single-purpose and/or single discipline literature reviews when not possible. Synoptic tables are provided, giving an overview of the multi-purpose platform concepts investigated, the numerical approaches adopted, and a comprehensive snapshot classifying the references discussed by industry (offshore renewables, aquaculture, both) and by aspect (technological, environmental, socio-economic). The majority of the multi-purpose platform concepts proposed are integrating only multiple offshore renewable energy devices (e.g. hybrid wind-wave), with only few integrating also aquaculture systems. MPPs have significant potential in economizing CAPEX and operational costs for the offshore energy and aquaculture industry by means of concerted spatial planning and sharing of infrastructure
Keywords: Social science; Wave Aquaculture; Offshore wind; Marine renewable energy; Multi use platform; Multi purpose platform